2022
DOI: 10.1002/jmv.28322
|View full text |Cite
|
Sign up to set email alerts
|

Inverted repeats in the monkeypox virus genome are hot spots for mutation

Abstract: The current monkeypox virus (MPXV) strain differs from the strain arising in 2018 by 50+ single nucleotide polymorphisms (SNPs) and is mutating much faster than expected. The cytidine deaminase apolipoprotein B messenger RNA editing enzyme, catalytic subunit B (APOBEC3) was hypothesized to be driving this increased mutation. APOBEC has recently been identified to preferentially mutate cruciform DNA secondary structures formed by inverted repeats (IRs). IRs were recently identified as hot spots for mutation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
4
9
0
Order By: Relevance
“…As with HIV, this effect may be a result of ITR genes at chromosome ends having a longer exposure time of ssDNA during replication than other genes within the chromosome (46). This finding is consistent with previous publications which found higher gene gain and loss activity at the ends (35) and a higher frequency of recent mutations in the MPXV inverted repeat regions (26).…”
Section: Many Monkeypox Virus Genes Show Over-representation Of Tc Ho...supporting
confidence: 91%
See 2 more Smart Citations
“…As with HIV, this effect may be a result of ITR genes at chromosome ends having a longer exposure time of ssDNA during replication than other genes within the chromosome (46). This finding is consistent with previous publications which found higher gene gain and loss activity at the ends (35) and a higher frequency of recent mutations in the MPXV inverted repeat regions (26).…”
Section: Many Monkeypox Virus Genes Show Over-representation Of Tc Ho...supporting
confidence: 91%
“…Although APOBEC3s have already been strongly implicated in the MPXV outbreak of 2022 (3,7,26,27), the question of how emerging MPXV strains will continue to undergo further APOBEC3-mediated mutations remains open. Thus, we have evaluated the potential for future evolution of the MPXV genome mediated by APOBEC3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously reported, we identified a strong mutation bias with a large majority of mutations (94%) being G > A (57%) and C > U (37%) in a dinucleotide context suggesting that they could have occurred because of genome editing by human APOBEC3 enzymes. This has been previously highlighted in several studies 5,13,41,42,48,52,67,70 . In addition, such signatures of APOBEC3 activity were prominent among clade IIb whereas not among other MPXV clades.…”
Section: Discussionsupporting
confidence: 62%
“…This has been previously highlighted in several studies. 5,13,41,42,48,52,67,70 In addition, such signatures of APO-BEC3 activity were prominent among clade IIb whereas not among other MPXV clades. Besides, interestingly, Forni et al 48 reported based on the analysis of 1,624 MKPV genomes and of experimental data for VACV infection that APOBEC3 signatures preferentially implicated highly expressed viral genes.…”
Section: Metagenomic Analysis Of Ngs Runsmentioning
confidence: 94%